Research on Financial Performance Evaluation of Pharmaceutical Listed Companies: Based on Factor Analysis and Cluster Analysis - Lu, Qianqian (Transactions on Economics, Business and Management Research, 2024)
With the improvement of people's living standards in China, people pay more and more attention to their own health. As one of the basic industries for people's livelihood, the pharmaceutical industry is often concerned. The article takes 85 pharmaceutical listed companies in China as the research object, selects 12 indicators from four aspects: profitability, debt paying ability, growth ability, and operational ability, and evaluates the financial performance of pharmaceutical listed companies based on factor analysis. By applying cluster analysis, 85 pharmaceutical listed companies were divided into 5 categories, providing more targeted and specific suggestions, creating conditions for the continuous optimization and development of pharmaceutical enterprises.